Evaluation of navigation based on system optimal traffic assignment for connected cars. (4th June 2020) - Wang, Weibin; Uehara, Minoru; Ozaki, Haruo
Recently, many cars have become connected to internet. In the near future, almost all cars will be connected cars. Such a connected car will automatically drive according to a navigation system. Conventional car navigation systems are based on User Equilibrium (UE) traffic assignment. However, System Optimal (SO) traffic assignment is better than UE traffic assignment. To realise SO traffic assignment, complete traffic information is required. When connected cars become ubiquitous, all traffic information will be gathered into the cloud. Therefore, a cloud-based navigation system can provide SO-based navigation to connected cars. An SO-based navigation method in which the cloud collects traffic information from connected cars, computes SO traffic assignments, and recommends SO routes to users was recently proposed. In this paper, we evaluate this SO-based navigation method in detail.